2009
DOI: 10.2131/jts.34.151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperprolactinemia on toxicological parameters and proliferation of islet cells in male rats

Abstract: INTRODUCTIONHyperprolactinemia is a common clinical disorder due to long-term administration of chemicals such as dopamine D2 receptor antagonists. The role of toxicological evaluation is to protect humans from toxicity induced by drugs or other chemicals and unwanted side effects. It is necessary to assess and differentiate direct toxicological effects of compounds from their secondary effects.The anterior pituitary-grafted rat is well known as a useful model animal for research on hyperprolactinemia; many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…rats: If due to effects of PRL, tubular profiles are more frequent and alveolar profiles are lined by smaller, cuboidal cells with basophilic cytoplasm; alveoli have a thinned epithelium Male rats or mice: humans. In male rats, xenobiotics that increase PRL will result in atrophy of alveoli resulting in a tubulo-alveolar appearance of the gland similar to what is observed in the normal virgin female gland (Figure15;Ose et al 2009;Lucas et al 2007). In both males and females, xenobiotics may perturb the hypothalamic-pituitary-gonadal axis resulting in a decrease in circulating, mammotrophic hormones resulting in glandular atrophy.…”
mentioning
confidence: 58%
“…rats: If due to effects of PRL, tubular profiles are more frequent and alveolar profiles are lined by smaller, cuboidal cells with basophilic cytoplasm; alveoli have a thinned epithelium Male rats or mice: humans. In male rats, xenobiotics that increase PRL will result in atrophy of alveoli resulting in a tubulo-alveolar appearance of the gland similar to what is observed in the normal virgin female gland (Figure15;Ose et al 2009;Lucas et al 2007). In both males and females, xenobiotics may perturb the hypothalamic-pituitary-gonadal axis resulting in a decrease in circulating, mammotrophic hormones resulting in glandular atrophy.…”
mentioning
confidence: 58%
“…Changes in glucose homeostasis in adult life, such as lower insulin secretion ( 59 , 60 ) , changes in insulin sensitivity ( 12 , 61 ) , higher glucogenolysis ( 62 ) , lower β-cell quantity and pancreatic content of insulin ( 63 ) are associated with protein malnutrition in critical periods of life. Moreover, PRL modulates the proliferation of pancreatic β-cells and the consequent lowering of glycaemia ( 64 ) . The fact that programmed EW rats had lower serum PRL could explain why they have an inappropriate response of insulin to hyperglycaemia have shown were adults, perhaps because they have an impairment on the development of pancreatic β-cells, Recently, we have shown that maternal hypoprolactinaemia for the last 3 d of lactation programmes for insulin resistance and lower serum PRL in their adult offspring ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that hyperglycaemia and failure of insulin to respond adequately, found in our present study, may be due to higher body fat. Several studies showed an important role of PRL on the proliferation of pancreatic beta cells (Cunha et al 2007; Huang et al 2009) and consequent lowering of glycaemia (Ose et al 2009). The fact that our programmed animals had lower PRL serum levels when adults, could explain why they have an inappropriate response of insulin to hyperglycaemia when adults, maybe because they have an impairment in the development of pancreatic beta cells.…”
Section: Discussionmentioning
confidence: 99%